Freshman EFL Learners’ Use of Attitude Verbs and Considerations in Their Propositional Attitude Expressions - Berlin Sibarani (Journal of Language, Literature and Teaching, 2021)
This study is intended to describe the underlying consideration of the Indonesian EFL learners in choosing attitude verbs to express their propositional attitude towards an object. The data of this study were elicited by asking the students to write their propositional attitudes towards familiar and unfamiliar pictures of objects. The familiarity of an object to the students were suspected to be one of the students’ considerations. The elicited written expressions were identified, classified and compared by using the concept of attitude verbs as the temporary predetermined perspective. The results of the identification and classification analysis show that propositional attitude was expressed in three ways: by using verbs of attitude of look, think and hidden verb attitude. The use of look (85%) dominates the other two verbs. The use of hidden verbs attitude occurs 12%, and the verb think is the least occurrence (3%). While the results of the comparison analysis show that familiarity of an object is not the only factor that the students consider in using attitude verbs. Their ability to think of what they see, that is labelled as psychological factor, and their sensitivity to the social effect of their propositional attitude, that is called as social factor, also influence their consideration in using the attitude verbs. Based on these results, it is concluded that the use of attitude words among the EFL learners is not only a reflection of their linguistic ability but also a reflection of their social sensitivity. Key Words: Attitude verbs, Consideration, EFL learners, Propositional attitude,